Recent advances in the research on effects of micro/nanoplastics on carbon conversion and carbon cycle: A review. (15th May 2023) - Shen, Maocai; Liu, Shiwei; Hu, Tong; Zheng, Kaixuan; Wang, Yulai; Long, Hongming
Abstract: Massive production and spread application of plastics have led to the accumulation of numerous plastics in the global environment so that the proportion of carbon storage in these polymers also increases. Carbon cycle is of fundamental significance to global climate change and human survival and development. With the continuous increase of microplastics, undoubtedly, there carbons will continue to be introduced into the global carbon cycle. In this paper, the impact of microplastics on microorganisms involved in carbon transformation is reviewed. Micro/nanoplastics affect carbon conversion and carbon cycle by interfering with biological fixation of CO2, microbial structure and community, functional enzymes activity, the expression of related genes, and the change of local environment. Micro/nanoplastic abundance, concentration and size could significantly lead to difference in carbon conversion. In addition, plastic pollution can further affect the blue carbon ecosystem reduce its ability to store CO2 and marine carbon fixation capacity. Nevertheless, problematically, limited information is seriously insufficient in understanding the relevant mechanisms. Accordingly, it is required to further explore the effect of micro/nanoplastics and derived organic carbon on carbon cycle under multiple impacts. Under the influence of global change, migration and transformation of these carbon substances may cause new ecological and environmental problems. Additionally, the relationship between plastic pollution and blue carbon ecosystem and global climate change should be timely established. This work provides a better perspective for the follow-up study of the impact of micro/nanoplastics on carbon cycle. Graphical abstract: Image 1 Highlights: Research progress on impact of micro/nanoplastics on carbon cycle is reviewed. Mechanisms of MPs affecting carbon cycle were systematically reviewed. Impact of MPs on blue carbon ecosystem reduce its ability to store CO2 . Plastic pollution affect marine carbon fixation capacity and global carbon cycle. Knowledge gaps and challenges of relevant research are proposed.